Environmental Impact Assessment of a Flood Control Channel in Sfax City, Tunisia - Noura Dahri; Abdelfattah Atoui; Habib Abida (International Journal of Science and Engineering, 2014)
The objective of this study is to evaluate water and sediment quality in the southern branch of a flood control channel in Sfax city, as well as its neighboring sites.  This artificial channel, located 4km away from downtown Sfax, was implemented in 1984 to protect the city against floods. Even though it contributed to reduce the harmful flood effects, this channel also resulted in new environmental problems that may cause a public health threat. Indeed, artificial surfaces pose a greater risk of infection due to bacteria, fungi and other microorganisms. A total of 19 water samples (9 from the channel and 10 from groundwater wells) were collected in a dry period and analyzed in the laboratory. Furthermore, 12 sediment samples were taken from the bottom of the channel. Water quality data were used to examine the spatial variability of the different water quality parametrs. The resultant maps revealed an important contamination and illustrated that the degree of contamination differs from one site to another, depending on the distance from the pollution source (industrial, domestic or agricultural activity), the depth of the groundwater table and also the maintenance of the well and its surroundings.